Caloplaca tornoënsis new to Finland - Kuusisto Inka; Mattanen Saana (Nordic Lichen Society, 2025)
Caloplaca tornoënsis is reported from Finland for the first time. Specimens were collected from five locations of NW Finland and from one location of NE Finland. Collections were made from snowbeds on bryophytes using transect plot-based sampling method. C. tornoënsis has a circumpolar distribution and it is probably overlooked, although a rare species in Finland. The species should be looked for in late melting areas of mountains of northernmost Finland.